Optimalisasi Kebijakan Ekonomi Publik dalam Mengatasi Eksternalitas, Barang Publik, Redistribusi Pendapatan, dan Penerapan Pajak Progresi - Awaliah Arisyah; Hendra Riofita (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
Public economic policy plays a crucial role in balancing market efficiency and social justice. This article aims to analyze how optimizing public policy can address major challenges such as negative externalities, limitations in public goods provision, income inequality, and unfair taxation systems. This study employs a qualitative approach through literature review focusing on recent academic works. The findings suggest that data-driven and holistic economic public policies can significantly contribute to enhancing social welfare and promoting inclusive economic growth. Strengthening implementation and fostering cross-sector collaboration are essential to ensure more targeted and sustainable policy outcomes.